Motivational EFL Teaching Strategies in Hybrid Learning for Non-English Majors at an Islamic University - Purwanti, Eko; Oktaviani, Heti Nur (Universitas Muhammadiyah Yogyakarta, 2026)
Motivational teaching strategies are widely recognized as a key factor in students’ success in language learning, particularly in English as a Foreign Language (EFL) contexts. Students from non-English academic backgrounds often require differentiated approaches to maintain engagement and support their learning process. This study explores the motivational strategies employed by EFL lecturers in a hybrid learning environment at an Islamic private university, focusing on students from non-English departments. Adopting a descriptive qualitative design, the study involved six lecturers who taught English in various departments, including Accounting, Economics, Civil Engineering, Mechanical Engineering, Nursing, and International Relations. Data were collected through in-depth interviews. The findings identify four main motivational strategies used by lecturers: implementing engaging and varied learning activities, providing constructive feedback, offering verbal encouragement, and ensuring consistent exposure to English in classroom interactions. The study also highlights three significant challenges faced by the lecturers: selecting appropriate teaching materials, accommodating students’ diverse language proficiency levels, and managing large class sizes. These insights offer practical implications for improving motivational practices in hybrid EFL instruction for non-English majors